2011
DOI: 10.1038/jhg.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive microRNA-133a regulates novel molecular networks in lung squamous cell carcinoma

Abstract: Analysis of the microRNA (miRNA) expression signature of lung squamous cell carcinoma (lung-SCC) revealed that the expression levels of miR-133a were significantly reduced in cancer tissues compared with normal tissues. In this study, we focused on the functional significance of miR-133a in cancer cell lines derived from lung-SCC and the identification of miR133a-regulated novel cancer networks in lung-SCC. Restoration of miR-133a expression in PC10 and H157 cell lines resulted in significant inhibition of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 34 publications
4
99
0
Order By: Relevance
“…However, a more recent study demonstrated that miR-133 is aberrantly expressed in tumors, and that miR-133a/b can inhibit the proliferation, and metastasis of bladder and prostate cancer by regulating the expression of the epidermal growth factor receptor (20,21). In addition, previous studies have observed a significant downregulation of miR-133a/b in head and neck neoplasms, lung cancer, esophageal cancer, colon cancer, renal carcinoma, prostate cancer, and other malignancies (22)(23)(24)(25). The present study indicated that miR-133b may act as a tumor suppressor while regulating the invasion and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 54%
“…However, a more recent study demonstrated that miR-133 is aberrantly expressed in tumors, and that miR-133a/b can inhibit the proliferation, and metastasis of bladder and prostate cancer by regulating the expression of the epidermal growth factor receptor (20,21). In addition, previous studies have observed a significant downregulation of miR-133a/b in head and neck neoplasms, lung cancer, esophageal cancer, colon cancer, renal carcinoma, prostate cancer, and other malignancies (22)(23)(24)(25). The present study indicated that miR-133b may act as a tumor suppressor while regulating the invasion and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 54%
“…A recent report concerning non-small cell lung cancer describes a relationship between the tumor stage and expression of miR133b (49,50). Acting through effects on epidermal growth factor receptor, miR133b appears to limit proliferation and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC cells both miR133a/133b target moesin specifically, and restoration of miR-133b levels in HNSCC cells, as well as in PC10 and H157 lung SCC cell lines, reduces moesin expression, inhibits cell proliferation, cell migration and invasion [143] . The phenotype is also associated with elevation of other miR133 targets such as ARPC5 and GSTP1 [115] . Both ARPC5 and GSTP1 levels are elevated in lungSCC and elevated GSTP1 is seen in bladder cancer (TCC) associated with reduced levels of miR133a [144] .…”
Section: Other Pleiotropic Pathwaysmentioning
confidence: 99%
“…Muscle microRNAs in development and disease [102,106] , metastatic lung tumors [107] , proliferating breast cancer [108] , ERαpositive breast cancer [109] , EEC [110] , NSCLC [85] , TSCC [111,112] , laryngeal SCC [113] , and HNSCC [114] (Table 3). Many of the reports identify reduction in a single myomiR, but in case studies of particular cancers often the different myomiRs have been identified as downregulated, for example in NSCLC tumor samples, miR1 [100] , 133a [85,115] , 133b [85,115] , 206 [107] or miR1/206 [99] have been reported, by implication dysregulation of all of the myomiRs. Si milarly, for colorectal cancer, downregulated miR1 [101] , 133a [104] , or 133b [86] , or upregulated miR206 [116] , while in prostate cancer downregulated miR1 [101,102] and miR206 [102] , miR133a [97,102] and miR133b [95,96] have been variously reported (Table 3).…”
Section: Cancer and Downregulated Myomirsmentioning
confidence: 99%